Bumdes Business Development Strategy Tunas Harapan Ujung Tanjung Village, Lebong Sakti District Lebong District - Putra Kurniawan Utama; Siti Hanila; Yun Fitriano (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The aim of the study was to determine the business development strategy for BUMDes Tunas Harapan, Ujung Tanjung Village, Lebong Sakti District, Lebong Regency. The sample in this study was 56 people, namely 6 BUMDes business managers and 50 residents of Ujung Tanjung Village, Lebong Sakti District, Lebong Regency. ).The result of the sum of the strengths possessed is 22.350 while the weaknesses are 11.60, then the internal factor quadrant is 22.350 – 11.60 = 10.75 meaning the ability of BUMDes Tunas Harapan Ujung Tanjung Village, Lebong Sakti District, Lebong Regency in utilizing the strengths and minimizing the weaknesses that exist internally. The opportunities that this strategy has are 20.05 and the threats are 11.59. Then the external factor quadrant is 20.05 – 11.59 = 8.46, meaning the high ability of BUMDes Tunas Harapan Ujung Tanjung Village, Lebong Sakti District, Lebong Regency in taking advantage of opportunities and overcoming threats faced by BUMDes in business development . The BUMDes Tunas Harapan strategy for Ujung Tanjung Village, Lebong Sakti District, Lebong Regency supports an aggressive strategy, or SO strategy in the SWOT matrix, namely optimizing performance by developing technology and utilizing village potential by establishing new business fields.